Millisecond dynamic of SARS‐CoV‐2 spike and its interaction with ACE2 receptor and small extracellular vesicles. Issue 14 (7th December 2021) - Lim, Keesiang; Nishide, Goro; Yoshida, Takeshi; Watanabe‐Nakayama, Takahiro; Kobayashi, Akiko; Hazawa, Masaharu; Hanayama, Rikinari; Ando, Toshio; Wong, Richard W.
Abstract: SARS‐CoV‐2 spike protein (S) binds to human angiotensin‐converting enzyme 2 (hACE2), allowing virus to dock on cell membrane follow by viral entry. Here, we use high‐speed atomic force microscopy (HS‐AFM) for real‐time visualization of S, and its interaction with hACE2 and small extracellular vesicles (sEVs). Results show conformational heterogeneity of S, flexibility of S stalk and receptor‐binding domain (RBD), and pH/temperature‐induced conformational change of S. S in an S‐ACE2 complex appears as an all‐RBD up conformation. The complex acquires a distinct topology upon acidification. S and S2 subunit demonstrate different membrane docking mechanisms on sEVs. S‐hACE2 interaction facilitates S to dock on sEVs, implying the feasibility of ACE2‐expressing sEVs for viral neutralization. In contrary, S2 subunit docks on lipid layer and enters sEV using its fusion peptide, mimicking the viral entry scenario. Altogether, our study provides a platform that is suitable for real‐time visualization of various entry inhibitors, neutralizing antibodies, and sEV‐based decoy in blocking viral entry. Teaser : Comprehensive observation of SARS‐CoV‐2 spike and its interaction with receptor ACE2 and sEV‐based decoy in real time using HS‐AFM.